2006
DOI: 10.1097/01.hjh.0000249695.81241.35
|View full text |Cite
|
Sign up to set email alerts
|

Introversion associated with large differences between screening blood pressure and home blood pressure measurement: the Ohasama study

Abstract: Physicians may need to be aware of 'introverted' patients who have high blood pressure in clinic settings, because they have the potential for 'white-coat' hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 25 publications
(33 reference statements)
0
10
0
Order By: Relevance
“…Anxiety and other forms of psychological distress, however, may have greater effects among those taking antihypertensive medications or who are otherwise aware of their hypertensive status [8, 9]. Apart from anxiety, studies of anger [10], depression [1113], and other neuroticism-related constructs [14, 15] have found inconsistent evidence for associations with the white coat effect. There has been comparatively less research on the role of other personality dispositions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Anxiety and other forms of psychological distress, however, may have greater effects among those taking antihypertensive medications or who are otherwise aware of their hypertensive status [8, 9]. Apart from anxiety, studies of anger [10], depression [1113], and other neuroticism-related constructs [14, 15] have found inconsistent evidence for associations with the white coat effect. There has been comparatively less research on the role of other personality dispositions.…”
Section: Introductionmentioning
confidence: 99%
“…There has been comparatively less research on the role of other personality dispositions. Among the few exceptions is a Japanese study that compared clinical screenings to home BP measurements in 666 individuals [15]. They found no associations with neuroticism, but introverted participants had a larger difference between the screening and the home systolic BPs.…”
Section: Introductionmentioning
confidence: 99%
“…Personality traits are also considered to be an important factor in functional decline risk. Several studies have reported that personality traits such as neuroticism, extraversion, anger, and hostility are significant predictors of mortality, and clinical health outcomes (Almada et al 1991;Wilson et al 2005;Hozawa et al 2006;Shipley et al 2007). Particularly in elderly populations, it has been hypothesized that these traits may affect subsequent physical health outcomes and mortality (Duberstein et al 2003;Wilson et al 2005;Krueger et al 2006;Hampson et al 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Our clinical experience is that the white coat effect seems to be prominent in shy and rather self-conscious patients, where the uncomfortable nature of the consultation with the patient drawn towards centre stage is the trigger for the blood pressure elevation. Data from a recent Japanese study supports this observation [9]. Hozawa et al found that white coat reactors scored low on the Eysenck extroversion scale (high introversion).…”
Section: Relation Of Psychological Stress To the Development Of Hypermentioning
confidence: 70%